Z+3=-6

Simple and best practice solution for Z+3=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Z+3=-6 equation:


Simplifying
Z + 3 = -6

Reorder the terms:
3 + Z = -6

Solving
3 + Z = -6

Solving for variable 'Z'.

Move all terms containing Z to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + Z = -6 + -3

Combine like terms: 3 + -3 = 0
0 + Z = -6 + -3
Z = -6 + -3

Combine like terms: -6 + -3 = -9
Z = -9

Simplifying
Z = -9

See similar equations:

| 2-12=z/-5 | | 7v-43=5(v-7) | | 7x-3x+3+7=26 | | 2(-8k+6)=12 | | x^2+x-8=2x | | 13x+4=18x-8 | | 9x-25=88 | | 3w-6w=24 | | 15x^2+34+15= | | 8x+8=9x-3 | | 6+3x=-x-6 | | y=-0.0002x^2+20x | | -30=-6v+3(v-2) | | 3x-1=1x+13 | | y=7x+0.4 | | 2xw=14 | | -4/3/(-8/9) | | x+2x+3x-6=12 | | -5b=-3b+-2b+-20 | | 5x+21/10=x/10 | | 8(w-8)=-8w-48 | | x+3x-7=13 | | j+45=79.50 | | 2(5x-8)+=-4x-13 | | x^3-7x+10x=0 | | 3.8x-3=2.8x | | -8m=-7m+-3 | | 10x-6x+4=20 | | 3(x+4)=-5x+12 | | 8x-14=98 | | 10m+-5m+6=5m-12 | | 4x-3x=27 |

Equations solver categories